Current Status and Analysis of Decoupling Mechanism - Qu Shuwei; Guo Zhihong (Jixie chuandong, 2022)
The decoupling configuration can achieve independent posture output through a specific drive, which can avoid many unnecessary output characteristics of the mechanism. The decoupling mechanism has broad application prospects for fast response time, low energy consumption and simple calibration. The unified type synthesis procedure is proposed through the comparative analysis of various decoupling type synthesis methods. The decoupling of the branch-chain constraint relationship is the key of the decoupling mechanism design. The constraint relation on the spatial direction and position of the kinematic pair axis is proposed. According to the influence of the arrangement order of the kinematic pair in the branch strand chain, the decoupling method is designed. Combined with the application of the decoupling mechanism in industry, precision engineering, medical treatment and bionic institutions, the research direction and application extension field of the decoupling mechanism are pointed out.